Tissue-specific fatty acids response to different diets in common carp (Cyprinus carpio L.). - Markus Böhm (Public Library of Science (PLoS), 2014)
Fish depend on dietary fatty acids (FA) to support their physiological condition and health. Exploring the FA distribution in common carp (Cyprinus carpio), one of the world's most consumed freshwater fish, is important to understand how and where FA of different sources are allocated. We investigated diet effects on the composition of polar and neutral lipid fatty acids (PLFA and NLFA, respectively) in eight different tissues (dorsal and ventral muscle, heart, kidney, intestine, eyes, liver and adipose tissue) of common carp. Two-year old carp were exposed to three diet sources (i.e., zooplankton, zooplankton plus supplementary feeds containing vegetable, VO, or fish oil, FO) with different FA composition. The PLFA and NLFA response was clearly tissue-specific after 210 days of feeding on different diets. PLFA were generally rich in omega-3 polyunsaturated FA and only marginally influenced by dietary FA, whereas the NLFA composition strongly reflected dietary FA profiles. However, the NLFA composition in carp tissues varied considerably at low NLFA mass ratios, suggesting that carp is able to regulate the NLFA composition and thus FA quality in its tissues when NLFA contents are low. Finally, this study shows that FO were 3X more retained than VO as NLFA particularly in muscle tissues, indicating that higher nutritional quality feeds are selectively allocated into tissues and thus available for human consumption.